1993
DOI: 10.1021/bi00210a026
|View full text |Cite
|
Sign up to set email alerts
|

Alternative model for mechanism-based inhibition of Escherichia coli ribonucleotide reductase by 2'-azido-2'-deoxyuridine 5'-diphosphate

Abstract: Ribonucleotide reductase (RDPR) from Escherichia coli is composed of two subunits, R1 and R2, and catalyzes the conversion of nucleotides to deoxynucleotides. The mechanism of inactivation of RDPR by 2'-azido-2'-deoxynucleoside 5'-diphosphate (N3UDP) has been examined using a variety of isotopically labeled derivatives: (1'-, 2'-, 3'-, or 4'-[2H])-N3UDPs and 2'-[15N3, 13C]-N3UDP. Electron paramagnetic resonance (EPR) and electron spin echo envelope modulation (ESEEM) spectroscopy studies using these compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 46 publications
6
77
1
Order By: Relevance
“…2 D-F). In retrospect, we have previously seen this type of behavior with another substoichiometric mechanism based inhibitor: 2Ј-azido-2Ј-deoxynucleotides, N 3 NDP (19,37,38). During a 2-min incubation of RNR with [5Ј-3 H] N 3 NDPs, Ͼ90% of RNR activity is lost, 50% of Y • is lost, and 0.7 eq radiolabel are associated with RNR.…”
Section: Discussionmentioning
confidence: 91%
“…2 D-F). In retrospect, we have previously seen this type of behavior with another substoichiometric mechanism based inhibitor: 2Ј-azido-2Ј-deoxynucleotides, N 3 NDP (19,37,38). During a 2-min incubation of RNR with [5Ј-3 H] N 3 NDPs, Ͼ90% of RNR activity is lost, 50% of Y • is lost, and 0.7 eq radiolabel are associated with RNR.…”
Section: Discussionmentioning
confidence: 91%
“…However, even for halides, the influence of a polar, hydrogenbonding environment may be substantial enough to force the heterolytic elimination mechanism favored in the enzyme-catalyzed transformation (Harris et al, 1984;Fernandes and Ramos, 2003). Extensive work on the reaction of N 3 UDP with wild-type enzyme (Salowe et al, 1993;van der Donk et al, 1995) can be rationalized by either the anionic release of azide (Pereira et al, 2003) or by initial homolytic generation of an azide radical and subsequent reduction to azide, in both cases followed by a sequence of N 2 elimination and addition to the C39 carbon atom. The N-centered radical generated in this latter step has only recently been characterized through a combination of high-field EPR spectroscopy and DFT calculations (Fritscher et al, 2005).…”
Section: Bereitgestellt Von | Universitaetsbibliothek Der Lmu Muenchenmentioning
confidence: 99%
“…On the basis of the results, it was proposed the thiyl radical at C225 13 reacted with the released hydrazoic acid (HN 3 ) to form a sulfinylimine radical 14. 24 In summary, the experimental data suggested that the inhibitory mechanism of RNR by N 3 UDP started with the abstraction of a hydrogen atom from the carbon at C3' by cysteinyl radical C439 to give 11. However, rather than releasing H 2 O upon oxidizing the hydroxyl group on C3', azide ion was released to form the ketyl radical 12.…”
Section: Proposed Mechanism On the Basis Of The Experimental Datamentioning
confidence: 96%
“…By double labeling of N 3 NDPs with 13 C and 15 N 3 and incubating with RDPR, Stubbe and Robins reported in 1993 that there was no hyperfine interaction between the nitrogen-centered radical and the 13 C nucleus, which suggested the cleavage of the nitrogen bond on the 2'-carbon (11⇒12). 24 Incubation of oxidized R1 and mutated cysteine proteins C225SR1 and C462SR1 with N 3 UDPs suggested the release of N 3 -, N 3 • , or HN 3 . On the basis of the results, it was proposed the thiyl radical at C225 13 reacted with the released hydrazoic acid (HN 3 ) to form a sulfinylimine radical 14.…”
Section: Proposed Mechanism On the Basis Of The Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation